Seismic Performance Evaluation of Wharf Based on ASCE 61-14 - Kukuh Adhi Kafie; Andreas Triwiyono; Iman Satyarno; Hu, Hsuan-Teh (Journal of the Civil Engineering Forum, 2023)
The adequacy of the structural performance of a wharf in withstanding seismic loads is of paramount importance. Therefore, this research aims to conduct an accurate pushover analysis on the adequacy of a wharf located in North Sulawesi, Indonesia. The study provides a comprehensive overview of the seismic performance of the wharf by examining displacement and strain parameters of its plastic hinge components under various loading conditions. To simulate accidental torsion, the wharf structure was analyzed by introducing variations in the eccentricity offset of the lateral pushover load of -5%, 0%, and 5% from the center of mass. The analysis of the torsion behavior involved a comprehensive examination of four control points located at each corner of the wharf plan. Additionally, the investigation took into account, the crucial aspect of soil-structure interaction by considering the equivalent fixity depth of the pile, which was used to evaluate the fixity length of the structure. In order to determine the target displacement of the wharf, analysis was performed in accordance with the established methodologies outlined in FEMA 356. It is also important to note that the seismic performance of the wharf was evaluated based on acceptance criteria in the form of strain limits imposed on various components, including concrete elements, reinforcing steel, and steel pipes, as prescribed by ASCE 61-14. In this study, a total of 30 models were examined, and the obtained results showed that the structure exhibited controlled and repairable damage even when subjected to a 475-year earthquake return period (CLE: Contingency Level Earthquake). Following this, the analysis of variations in displacement control point served to determine the inherent torsion exhibited by the structure, and the introduction of different lateral load eccentricity offsets and variations in pushover loading direction were found to contribute to the increased displacement and strain in the plastic hinge components.